EKSPLORASI SIKAP SISWA MADRASAH ALIYAH SALAFIYAH SYAFI’IYAH DALAM MENGHADAPI : EKSPLORASI SIKAP SISWA MADRASAH ALIYAH SALAFIYAH SYAFI’IYAH DALAM MENGHADAPI TANTANGAN MORAL DI ERA INTEGRASI NASIONAL - Al Ghifroni, Abi Khasan; Abror Rosyidin, Muhammad (Al Tadib : Jurnal Ilmu Pendidikan, 2026)
Abstract: The era of national integration, shaped by globalization and the advancement of digital technology, presents complex moral challenges for students, particularly in relation to attitudes toward diversity, social media ethics, and civic responsibility. In this context, students’ moral attitudes serve as a strategic indicator of the success of character education in madrasahs. Although students in the religious track at Madrasah Aliyah Salafiyah Syafi’iyah receive intensive religious instruction intended to strengthen their moral resilience, there are indications of a disparity between the normative values taught and students’ social practices amid the pervasive influence of digital media. This study aims to explore the understanding and implementation of moral values among eleventh-grade religious-track students, to identify moral challenges within the landscape of national integration, and to analyze students’ responses based on the religious values they have internalized. The research employs a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed systematically through data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and prolonged observation. The findings indicate that moral education at Madrasah Aliyah Salafiyah Syafi’iyah is implemented integratively through formal classroom instruction, religious activities, and character development programs. The internalization of Islamic values fosters tolerant attitudes and social responsibility among students, as reflected in the consistency of their behavior amid the dynamics of national integration. Keyword: Exploration, Students’ Attitudes in Religious Educational Institutions, Morality, National Integration